Personal Financial Planning and Management during Covid-19 Pandemic by Strengthening Financial Literacy for Generation Z in Condongcatur, Kapanewon Depok, Sleman Regency, Special Region of Yogyakarta: Perencanaan dan Pengelolaan Keuangan Pribadi selama Pandemi Covid-19 dengan Penguatan Literasi Keuangan bagi Generasi Z di Condongcatur, Kapanewon Depok, Kabupaten Sleman, D.I. Yogyakarta - Ratri Paramitalaksmi; Wuku Astuti (Mattawang: Jurnal Pengabdian Masyarakat, 2022)
This Community Service aims to provide education about financial planning and financial management as well as strengthen insights into the benefits and risks of various financial facilities for Generation Z in Condongcatur, Kapanewon Depok, Sleman Regency, Special Region of Yogyakarta. Education on understanding financial planning was given to Generation Z in Condongcatur, Kapanewon Depok, Sleman Regency, Special Region of Yogyakarta by means of Online Training and Focus Group Disscusion through Google Meeting on July 20th – 21st, 2022 which was attended by 52 participants consisting of young people in the Condongcatur neighborhood. This Community Service has been carried out according to plan. The large number of questions from the participants indicated that the high interest of participants to learn about financial literacy. Displaying examples of financial products, both in the form of products that can be used as an investment products from the banking and non-banking industries, can make it easier for participants to visualize in the delivery of information during the Community Service. Abstrak Pengabdian Kepada Masyarakat (PKM) ini bertujuan untuk memberikan edukasi tentang perencanaan keuangan dan pengelolaan keuangan serta memperkuat wawasan tentang manfaat dan risiko berbagai fasilitas keuangan bagi para Generasi Z di Kelurahan Condongcatur, Kapanewon Depok, Kabupaten Sleman, D.I. Yogyakarta. Edukasi pemahaman perencanaan keuangan diberikan kepada para Generasi Z di lingkungan Kelurahan Condongcatur, Kecamatan Depok, Kabupaten Sleman, D.I. Yogyakarta dengan cara Pelatihan Online dan Focus Group Disscusion (FGD) melalui Google Meeting pada tanggal 20 – 21 Juli 2022 yang diikuti oleh 52 peserta yang terdiri dari para Generasi Z di lingkungan Kelurahan Condongcatur, Kecamatan Depok, Kabupaten Sleman, D.I. Yogyakarta. Pengabdian Kepada Masyarakat (PKM) ini telah dilaksanakan sesuai rencana. Jika dilihat dari banyaknya pertanyaan dari para peserta menunjukkan bahwa tingginya minat peserta untuk belajar tentang literasi keuangan. Contoh produk keuangan yang ditampilkan, baik dalam bentuk berbagai produk investasi dari sektor perbankan maupun non-perbankan dapat memudahkan para peserta untuk memvisualisasikan dalam penyampaian informasi selama PKM berlangsung.